DECISION OF VEHICLE CONSUMER PURCHASE ON STUDENTS IN MAKASSAR CITY - Safar, Ilham; Sari, Novita Kumala (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2018)
This study aims to determine the motive of purchasing hijab decision among female students in Makassar. This study was conducted on female students in Makassar. Purchasing decisions are the demands of problem solving needs faced by consumers. Jilbab is an obligation for a Muslim woman. The current development of headscarf users makes the hijab a popular lifestyle in many circles. Student is one of the consumer of hijab today. This research is a qualitative research with descriptive analysis approach. The data in this study were collected through the technique of Library Research (Library Research) and Field Research (Field Research) by way of Interview and Observation. In this research there are 15 informants who are entirely female students in several campuses in Makassar city. The results of this study conclude that the motive of purchasing hijab decision in female students in the city of Makassar due to the assumption that the appearance of hijab in the current era is increasingly attractive to wear by mixing and covering the hijab with everyday clothes.Â